Emergency triage - Mackway-Jones, Kevin; Marsden, Janet; Windle, Jill (John Wiley & Sons Inc., 2014)
The Manchester Triage System (MTS), the most widely used emergency medical triage system in the UK and Europe, is employed to prioritise the treatment of tens of millions of patients each year. MTS utilises an easy-to-understand and safe, risk-based system of prioritisation. This title contains all the information necessary for an MTS user.